WOMEN ENTREPRENEURSHIP IN HARYANA -PROBLEMS AND PROSPECTS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research delves into the primary determinants that impact women's entrepreneurship, emphasizing the incentives and obstacles encountered by female entrepreneurs. The study looks at how factors including years of business experience, marital status, and educational background affect entrepreneurial objectives like being independent, improving family welfare, and changing society, using data from 123 respondents. The results show that women entrepreneurs are motivated by a combination of social and personal objectives, with financial independence and family support standing out as key drivers.However, depending on their educational background and business development stage, women can encounter a variety of obstacles. Among the main challenges are lack of funds, social hurdles, work-life balance concerns, and gender discrimination. The study also emphasizes the importance of education, demonstrating that women who have completed more school report fewer obstacles than do their male counterparts. It's interesting to note that the findings show that women who are just starting out in company face higher societal and financial barriers than women who have been in the industry longer. Despite these revelations, the study has certain drawbacks. The small sample size and geographic focus may have contributed to the results' limited generalizability. Additionally, self-reported data is used in the study, which increases the risk of bias. The results indicate that helping women entrepreneurs requires tackling societal and financial constraints, especially in the early phases of entrepreneurship. To encourage women's entrepreneurship, policymakers should concentrate on establishing an enabling environment that includes financial access, skill development, and gender-equal laws. The understanding of women's entrepreneurial journeys will be further enhanced by broadening the scope of research across various industries and countries.